Missing in (Collective) Action: Ideology, System Justification, and the Motivational Antecedents of Two Types of Protest Behavior - Jost, John T.; Becker, Julia; Osborne, Danny; Badaan, Vivienne (Current directions in psychological science : a journal of the American Psychological Society, 2017)
Social-psychological models of collective action emphasize three antecedents of protest: (a) anger at perceived injustice, (b) social identification, and (c) beliefs about group efficacy. These models are extremely useful but have rarely incorporated ideological factors—despite the fact that protests occur in societal contexts in which some people are motivated to defend and bolster the status quo whereas others are motivated to challenge and oppose it. We adopt a system-justification perspective to specify when individuals and groups will—and will not—experience moral outrage and whether such outrage will be directed at defenders versus critics of the status quo. We describe evidence that epistemic, existential, and relational needs for certainty, security, and affiliation undermine support for systemchallenging protests by increasing system-defensive motivation. We also discuss system-based emotions and backlash against protestors and propose an integrated model of collective action that paves the way for more comprehensive research on the psychological antecedents of social change.